2020
DOI: 10.1016/j.jbusres.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

When and how frontline service employee authenticity influences purchase intentions

Abstract: In this manuscript, we investigate the central role of perceived frontline service employee (FSE) authenticity and the process by which it impacts purchase intentions, taking into account the represented brand's authenticity. While brand authenticity has previously been shown to enhance consumer outcomes, we find that FSE authenticity is a separate significant predictor of purchase intentions. Further, we find that FSE authenticity enhances purchase intentions by increasing perceived trust and perceived qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
(83 reference statements)
1
22
0
Order By: Relevance
“…As shown in Table 1, prior research is limited to human elements, particularly frontline service employees who interact with customers. For example, researchers widely examined the influence of service employees' authenticity during their encounters with customers on customers' perceived service quality and satisfaction (Andrzejewski and Mooney, 2016;Lechner and Mathmann, 2020;Lechner and Paul, 2019;Matthews et al, 2020;Yoo and Arnold, 2019). Furthermore, Kraak and Holmqvist (2017) investigated the influence of service employees' language use on the perceived authenticity of a service.…”
Section: Service Authenticity: a Conceptualization And Modelmentioning
confidence: 99%
“…As shown in Table 1, prior research is limited to human elements, particularly frontline service employees who interact with customers. For example, researchers widely examined the influence of service employees' authenticity during their encounters with customers on customers' perceived service quality and satisfaction (Andrzejewski and Mooney, 2016;Lechner and Mathmann, 2020;Lechner and Paul, 2019;Matthews et al, 2020;Yoo and Arnold, 2019). Furthermore, Kraak and Holmqvist (2017) investigated the influence of service employees' language use on the perceived authenticity of a service.…”
Section: Service Authenticity: a Conceptualization And Modelmentioning
confidence: 99%
“…Prior studies have also confirmed that when consumers evaluate credence services, as opposed to experience services, they do not prefer uniform criteria that are relatively easy to measure, such as the non-alignable and intangible attributes of the service and the reliability of the service provider (Sun et al. , 2012; Ding and Keh, 2017; Matthews et al. , 2020).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Moreover, intangibility and nonstandard attributes of services prompt consumers to form abstract and decontextualized perceptions of what credence services should include (Szpunar and McDermott, 2008), which intensifies their uncertainties and risk perceptions of such services. Prior studies have also confirmed that when consumers evaluate credence services, as opposed to experience services, they do not prefer uniform criteria that are relatively easy to measure, such as the non-alignable and intangible attributes of the service and the reliability of the service provider (Sun et al, 2012;Ding and Keh, 2017;Matthews et al, 2020). When consumers consider accepting robot services, they evaluate the expected service quality of the robot.…”
Section: Robot Services Service Types and Social Classmentioning
confidence: 99%
“…The present study is based on the widespread acknowledgment that brand authenticity is linked to consumers' subjective evaluations of the genuineness of a brand (Napoli et al , 2014). It is a construct that can determine individuals' behaviors by evoking positive perceptions such as genuineness, integrity and honesty (Baker et al , 2014; Matthews et al , 2020), which may lead consumers to form emotional bonds with brands (Fritz et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%